O sistema internacional de patentes e a saúde global: as implicações no controle das doenças tropicais negligenciadas no Brasil - Aires, Marco Antônio Pontes (2018)
The technological advances made in recent decades have contributed to facilitate the processes of communication and interaction between the various sectors of society. He realized that the social and economic implications, from the technological revolution, were increasing and changed the relations affecting the way we live in the social environment. In this context, it has been observed that the phenomenon of globalization is being consolidated, providing not only the increment of economic activities, but also the development of trade relations, whose impacts reflected in the International Patent System. Such a system arose from the need to establish international regulations to equalize the existing national laws on the protection of which came from the intellect, called Intellectual Property. This Institute was responsible for include the protection of industrial, scientific, artistic and literary. In terms of the industrial field, it can be seen that the issues relevant to the pharmaceutical industry suffered changes since the advent of the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement). The TRIPS Agreement, instrument maximum protection for patents, enabled the monopoly in the pharmaceutical field and the consequent control of specific portion of the market, interfering too much in the production of medicines. The consequences in the field of health were flagrant violation, since the investments in research carried out by large corporations intended to meet certain market niches, which demanded the creation of medicines for high value and geared to the more affluent strata of the population. In this way, to provide care for diseases that affect the most vulnerable populations, determining the emergence of Neglected Tropical Diseases and affecting the Global Health. These diseases are characterized by not being a priority in the framework of policies and services in health, and its prevalence; it is usually in developing countries, which, geographically, are arranged around the tropics, where there is a higher incidence of infectious diseases due to climate change. In Brazil, the neglected diseases these are considered a public health problem affecting a large part of the population, causing diseases and, in many cases, death. Configures itself as Tropical Diseases Neglected pathologies such as: Dengue, leishmaniosis, Chagas disease, tuberculosis, malaria, schistosomiasis, among others. In this way, the study on canvas had scope to analyze to what extent the current model of the patent system can impact on Global Health, regarding the eradication of neglected tropical diseases in Brazil. The approach was that the dialectical method, from the processes of conflict, which permeate the rights relating to the protection of patent holders and the right to health and in the procedure adopted is the historical method and structuralist. In addition, the systemic theory in the thoughts of Fritjof Capra is used as basic theory, having in view that all elements to be studied are inserted into a "web". It was concluded that the present study points to a revision in the current Model of the Patent System.